Phonation after cervical spinal cord injury (CSCI): Prospective case examinations of the acute and sub-acute stages of recovery. (June 2013) - MacBean, Naomi; Ward, Elizabeth; Murdoch, Bruce; Cahill, Louise; Geraghty, Timothy
Abstract The aim of the investigation was to examine the changes in phonation and related quality-of-life in the acute and sub-acute stages of recovery post-cervical spinal cord injury (CSCI). A prospective examination of phonation was conducted using perceptual and instrumental measures of respiratory and laryngeal functioning alongside a quality-of-life rating scale. Change was present across measures for both cases at each time point. Overall, a general pattern of recovery was seen, although some areas deteriorated between 6–12 months. Severity of impairments, extent of change, and impact on quality-of-life differed between the cases. Measures varied in sensitivity to change in function. Phonation can be impaired following both complete and incomplete CSCI, with type and severity of impairment/s undergoing change throughout the acute and sub-acute period post-injury. Spontaneous physiological recovery does not necessarily result in improved phonation and/ or quality-of-life. Potential exists for targeted speech-language therapy in this population, throughout recovery, to best capitalize on the physical changes that are occurring and to maximize functional application of skills to improve quality- of-life. Further research is warranted to examine this recovery period on a larger scale.